EVALUASI OPERASI PANGAN RIAU MAKMUR (OPRM) DI KABUPATEN SIAK TAHUN 2009-2013 (STUDI KASUS KECAMATAN BUNGA RAYA) - Nur, Siti Hazzah; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research aims to describe evaluation of implementiation The OperasiPangan Riau Makmur (OPRM) at Siak Regency from 2009 until 2013 especiallyon Bunga Raya Subdistrict hibiscus which is the granary in Siak. This programwas implemented by The government of Riau Province as mean to build foodsecurity as a legitimacy between the governor of Riau and the regent of SiakNumber: kptsn.580/VI/2012. The success of a program was evaluated be bassedon theory by William N. Dunn that is; effectiveness, efficiency, adikuacy, evendistribution, respon and accuracy program. The function of this program is asinforman substance about process of interaction as a crucial factor in the periodof implementation of the program so as to provide advice to the government,especially the implementation team to make this program success and to know theshortcomings and obstacles that occur.Methods used in this study is (kyu)alitative methods of data that can not berealized in the form of numbers, but in the form of an explanation that describesthe shape of the state, process, certain events. Data collection techni(kyu)uesusing interview techni(kyu)ues and documentation.From the research, The Operasi Pangan Riau Makmur (OPRM) at SiakRegency from 2009 until 2013 especially on Bunga Raya Subdistrict can becategorized not succeded. It seen from the failure to achieve self sufficiency inrice in Siak with many middlement out of town who come to buy particular fieldcrop farmers. Constrained case. Therefore, the advice given at the end of thestudy is how to address the issue during the period of implementation of foodsecurity so that the program can be maximum in implementation.Keywords: evaluation, food security, OPRM